Pravni učinek vpisa družbenika v register - Prostor, Jerneja (Podjetje in delo, 2022)
With the amendment ZGD-1I, the legislator has tried to ensure that the register entries of limited liability companies' members are up to date. Therefore, it changed the assumption as to who is considered to be the holder of the business share in relation to the company. According to the amendment, this is only the person who is entered in the court register. In this article, the author explains some of the views that have been expressed in literature and case law regarding this change. She concludes that the entry of a member in the register is still declaratory and does not affect the circumstance of who is the legitimate holder of a business share and corporate rights. This also means that the company must invite members to the general meeting, which does not necessarily mean those who are registered as members in the court register. Namely, the assumption can be contested. Furthermore, the author also addresses the deficiencies in the regulation that result from the mentioned change of the assumption.
Keywords: amendment ZGD-1I; amendment ZGD-1K; družba z omejeno odgovornostjo; entry of a member in the register; invitation to the general meeting; limited liability company; novela ZGD-1I; novela ZGD-1K; prenos poslovnega deleža; transfer of business share; vabilo na skupščino; vpis družbenika v register